Working Dog Structure: Evaluation and Relationship to Function - Zink, Chris; Schlehr, Marcia R. (Frontiers in Veterinary Science, 2020)
Working dogs help to keep society and individuals safe, secure, and healthy. To perform their varied functions, it is critical to select dogs that are structurally sound and capable of demonstrating power, coordination and agility. Characteristics such as size and substance, head and axial skeletal structure, chest size and conformation, and thoracic and pelvic limb angulation should be evaluated to select the optimal combination of characteristics to suit the tasks to which each dog will be assigned. This review provides guidance on how to evaluate each of these structural components and discusses the contributions of those body parts to a working dog’s function.